IDENTIDADES MÓVEIS NA OBRA DE PRYSCILA VIEIRA: GÊNERO E REPRESENTAÇÃO - Rodrigues, Camila (2015)
From birth, the woman is assigned the role of wife and mother. However, from modernity, a new social role, acquired by their insertion in the labor market. This will entail changes to the constitution of female identity generated from the new discursive practices. This new role will influence social relationships, changing the feminine identity construction. This paper analyzes the work of a cartoonist from Paraná Pryscila Vieira, creator of Amely character a real woman, trying to understand how does the representation of women in comics. Gender studies provide us with a theoretical corpus of reasonable proportion which seeks to establish the instruments necessary to read not only the texts, but also the conditions of production and circulation of works produced by women. And are based on feminist theories dedicated to question the binary view of gender as well as the contributions of cultural studies, debating the question of identity in contemporary times, our analysis reflects on the (de) construction of the (s) identity (s) female (s) in Vieira de comics, addressing especially the relationship between sexuality and this body in their productions, highlighting the new configurations of female identity. This study results from a literature search, hermeneutics and qualitative, in which, based on the theoretical lift, proceeded to the content analysis of the stories in selected comic and produced by Pryscila Vieira, understood as a set of research techniques aimed It is the search for meaning or sense of a document.